2020
DOI: 10.1111/bph.15002
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell and T‐cell crosstalk: Targeting metabolism as a therapeutic approach in chronic inflammation

Abstract: The role of metabolic reprogramming in the coordination of the immune response has gained increasing consideration in recent years. Indeed, it has become clear that changes in the metabolic status of immune cells can alter their functional properties. During inflammation, T cells need to generate sufficient energy and biomolecules to support growth, proliferation, and effector functions. Therefore, T cells need to rearrange their metabolism to meet these demands. A similar metabolic reprogramming has been desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 163 publications
0
16
0
Order By: Relevance
“…Endothelial cells are one of the main components of the retinal microvasculature, which is essential for retinal function (34). They play an important role in both inflammation and angiogenesis in DR (15) and are critical in attracting immune cells to sites of inflammation (35). Inflammatory cells produce angiogenic cytokines and growth factors, which in turn activate the microvascular endothelium, which expresses pro-inflammatory molecules (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells are one of the main components of the retinal microvasculature, which is essential for retinal function (34). They play an important role in both inflammation and angiogenesis in DR (15) and are critical in attracting immune cells to sites of inflammation (35). Inflammatory cells produce angiogenic cytokines and growth factors, which in turn activate the microvascular endothelium, which expresses pro-inflammatory molecules (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…A T-cell mediated immunity via antigen-specific crosslinking may be implicated ( 29 , 30 ). The ECs regulate key aspects of the immune system, particularly the recruitment and activation of T cells ( 31 , 32 ). Specifically, the ECs can activate effector/memory CD4 and CD8 lymphocytes and promote the expansion of one T cell subtype over another (helper, cytotoxic, or regulatory).…”
Section: Discussionmentioning
confidence: 99%
“…TECs are known to be particularly important for T cell recruitment and activation. Previous studies have shown that the interaction between T cells and ECs plays an important role in the regulation of the immune system during chronic inflammation ( 106 ). TECs in the tumor microenvironment are particularly relevant to circulating immune cells.…”
Section: The Pro-tumorigenic Effect Of the Relationship Between Strom...mentioning
confidence: 99%